Modulation of Inflammation in Heart Failure: The Role of Ziltivekimab and Canakinumab - Wołowiec, Łukasz; Zukow, Walery; Pęcherz, Julia; Czaplińska, Daria; Jaśniak, Albert; Grześk, Grzegorz (Journal of Education, Health and Sport, 2024)
This article examines the role of inflammation in heart failure pathogenesis and explores novel therapeutic strategies targeting inflammatory pathways. The increasing prevalence of heart failure, particularly those with preserved ejection fraction (HFpEF), highlights the urgent demand for effective treatments. Canakinumab, a monoclonal antibody targeting interleukin-1β, has shown promise in reducing cardiovascular events by modulating inflammation, while Ziltivekimab, a newer monoclonal antibody targeting interleukin-6, demonstrates potential in heart failure patients with elevated inflammatory markers. The article reviews clinical trials, including CANTOS and RESCUE, providing evidence of the efficacy of patient outcomes. The findings underscore the importance of personalized treatment strategies on heart failure, with a focus on inflammation-driven pathways, positioning anti-inflammatory therapies as a significant advancement in cardiovascular disease management. Future research will determine the broader clinical applicability of these therapies in managing heart failure, its complications, and fostering more favorable outcomes.